Fast functionalization of (7‐aza)indoles using continuous flow processes. Issue 3 (29th February 2016) - D'Attoma, Joseph; Cozien, Grégoire; Brun, Pierre Louis; Robin, Yves; Bostyn, Stéphane; Buron, Frédéric; Routier, Sylvain
Abstract: The use of flow chemistry to obtain (7‐aza)indole derivatives was investigated in three steps ( C‐ 3 iodination followed by N‐Boc protection). Excellent yields were achieved after very short reaction times. The challenge of using a continuous flow process was incremented by performing a novel copper‐free Sonogashira cross coupling in C‐ 3 (7‐Aza)indolic position using a recyclable supported palladium catalyst. A library of polyfunctionalized (7‐aza)indoles was obtained in high yield with a very efficient process (< 3 min.). Scale‐up was studied and the preparation of significant amounts of final alkynyl and Boc protected (aza)indoles can be immediately extended to a pilot scale in optimum security conditions. Abstract : An efficient and convenient methods have been developed for the polyfunctionnalizations of (7‐aza)indoles derivatives using flow chemistry. The final compounds were obtained in very good yields with a very efficient process and high compatibility with various chemical functions.